(3GdgjFI GdSfjI aj GdgjFI GdSfjIs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3YHO Gddg YKeGf Hf CHj HcQs)
(3ChdgG (B:s
(3GdMeO ddg GdPj YdefG eG de fcf fYde gPG cJGH aj Yde GdgjFI GbJHSJg ef GdBKGQ hSejJg HGdgjFI GdSfjI aj GdgjFI GdSfjIs
(3BNQgG (B:s
(3bGd(B: (3bdJ dYHO Gddg Hf YeQ eeG Ndb GdNdb bGd ef eGA hQjM hfhQ hXdeI aSCdJ GHf YHGS Yf Pdc abGd ceG bGd GHf YeQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3cTa GdXfhf(B: 2 / 2047s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3gjFIs